ANALISIS KOMPETENSI PEDAGOGIK GURU PENDIDIKAN PANCASILA BERLATAR BELAKANG NON-KEPENDIDIKAN DALAM PEMBELAJARAN DI SMP NEGERI 31 KERINCI - Rohmi Ardiansah; Hendra; Nurmalia Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the pedagogical competence of Pancasila Education teachers with non-education academic backgrounds and to identify the factors that hinder them in the learning process at SMP Negeri 31 Kerinci. The background of this problem stems from the presence of teachers with academic backgrounds in Public Administration and Government Science who teach the subject, which affects classroom instruction. This study used a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The informants involved were the school principal as the main informant, the teachers concerned as key informants, and students as additional informants. The results show that teachers' pedagogical competence has run fairly well in preparing teaching modules and utilizing basic technology, but overall it is still in an adaptation stage. Classroom management and approaches to students tend to be reactive, and evaluation still focuses on low-order cognitive skills (LOTS) without a systematic attitude assessment rubric. This condition is influenced by several inhibiting factors, such as limited basic pedagogical competence, facility constraints that trigger dependence on textbooks, and difficulty adjusting module time allocation to classroom dynamics. In addition, teachers also face constraints in adapting to the administration of the Merdeka Curriculum and difficulty designing evaluation instruments based on Higher Order Thinking Skills (HOTS). Overall, it can be concluded that although non-education background teachers have shown willingness, adaptation efforts, and good professional responsibility, their pedagogical competence has not yet fully reached the ideal standard, so continuous capacity building through structured training and mentoring is still needed.